Interfacial shear strength of Polylactic Acid-Kenaf fibre biocomposites - Anuar, Hazleen; Ahmad, Zuraida; Morlin, B.; Kovacs, J. G. (Trans Tech Publications, Switzerland, 2011)
This paper reported the interfacial shear strength (IFSS) between kenaf fibre (KF) and polylactic acid (PLA) matrix which was measured using microbond tests device. The value of IFSS obtained in PLA-KF is comparable to other polymer with natural fibre reinforcements. The properties of single kenaf fibre was determined from tensile tests and also described in this paper. From single kenaf fibre properties, various mechanical properties can be estimated for various applications.